Pollution effects on biochemical pathways determined in the polychaete Hediste diversicolor collected in three Portuguese estuaries. Issue 9 (8th August 2016) - Nunes, B.; Vidal, D.; Barbosa, I.; Soares, A. M. V. M.; Freitas, R.
Abstract : Biomonitoring is an important tool for the assessment of the quality and functions of ecosystems, providing information about the pollutants present and the direct effects that they exert on organisms. Abstract : Biomonitoring is an important tool for the assessment of the quality and functions of ecosystems, providing information about the pollutants present and the direct effects that they exert on organisms. Biomonitoring relies upon the quantification of variables that can be biochemical, genetic, morphological and physiological changes. Such variables are designated as biomarkers, and multiple biomarkers are usually determined simultaneously in order to have a more integrated analysis and information about sublethal early effects of contaminants. In this work, we quantified biomarkers, associated with oxidative stress (glutathione- S -transferases GSTs, and catalase CAT, activities; levels of peroxidative alterations, by the thiobarbituric acid reactive substances assay, TBARS) and neurotoxicity (acetylcholinesterase activity, AChE) in the polychaete Hediste diversicolor . Organisms were collected at three distinct estuaries, Ria de Aveiro (Laranjo and São Jacinto), Douro River (São Paio, Afurada, and Ribeira da Granja), both impacted by human activities, and Minho River (Seixas), which has been used as a reference site. Obtained data showed the occurrence of anti-oxidant responses, in most samples from contaminated sites, which was not followed however by the occurrence of oxidative damage in organisms from Ria de Aveiro. None of the analyzed organisms had significant impairment of cholinesterasic activity, suggesting the absence of a prior exposure to neurotoxic compounds. In fact, organisms collected at Ria de Aveiro had largely increased AChE activity, suggesting an uncommon paradoxical biological response that is further discussed.